A Guide to the Ingredients of Over-the-Counter Moisturizers for Psoriasis. Issue 1 (March 2014) - Chularojanamontri, Leena; Wongpraparut, Chanisada; Silpa-archa, Narumol; Pongparit, Kamolwan
It is believed that moisturizers can improve the efficacy of treatment for psoriasis. This study sought to analyze the active ingredients and properties of moisturizers that claimed to be suitable for psoriasis. Moisturizers for psoriasis were identified on electronic markets using the search terms "moisturizers" and "psoriasis." Forty-seven moisturizers that claimed to be suitable for psoriasis were identified. Vitamin E was the most common ingredient used for emollient properties. Of the 47 moisturizers, 35 (74%) contained anti-inflammatory properties and 12 (26%) contained keratolytic properties. Coal tar, low-potency corticosteroids, and botanical extracts were added for anti-inflammatory properties while salicylic acid, lactic acid, and ≥ 10% urea cream were used for keratolytic effect. Although it seems that each active ingredient added into moisturizers for psoriasis can decrease the severity of psoriasis, there is a lack of well-done studies on the over-the-counter preparations. Therefore, the recommendations to use them are currently not evidence-based.